Treatment of Widespread Granuloma Annulare with Adalimumab: A Case Report - Kozic, Heidi (Matrix Medical Communications, 2011)
The authors report a case of widespread granuloma annulare that was resistant to multiple systemic therapies, but responded rapidly to a short course of adalimumab.